The early pattern of human corpus callosum development: A transvaginal 3D neurosonographic study. (2nd June 2020) - Birnbaum, Roee; Barzilay, Ran; Brusilov, Michael; Wolman, Igal; Malinger, Gustavo
Abstract: Objective: To provide an in‐vivo description of early corpus callosum (CC) development. Methods: We reviewed 3D US volumes acquired transvaginally (TVUS) through the anterior fontanelle, between 14 to 17 weeks. The following landmarks were recognized: tela‐choroidea (TC), foramina of Moro, early CC and the evolving cavum septi pellucidi. The following measurements were taken: total, anterior and posterior sections, and height of the CC (referenced to the anterior TC border). All measurements were correlated to both the gestational age and the transverse cerebellar diameter (TCD). Results: Eighty nine volumes were included in the study (mean 15.1 weeks ± 0.84, TCD range, 13.1‐18.4 mm) with high inter and intra observer correlation of the measurements. We found high correlation between CC length and height, and TCD. The anterior segment of the CC appear earlier than the posterior one, and growth continues bi‐directionally. Initially, the posterior elongation is significantly larger than the anterior one. Association of all CC measurements with TCD remained significant when co‐varying for maternal age and fetal sex. Conclusions: imaging the fetal CC is feasible from 14 weeks by TVUS, by following the suggested insonation approach. The early CC develops bi‐directionally, and the posterior elongation is more significant than the anterior one.